2023
DOI: 10.3389/fnut.2022.1071284
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum ZJUIDS14 alleviates non-alcoholic fatty liver disease in mice in association with modulation in the gut microbiota

Abstract: This present study was designed to explore the protective role of Lactobacillus plantarum ZJUIDS14 against Non-alcoholic Fatty Liver Disease (NAFLD) in a high-fat-diet (HFD)-induced C57BL/6 mice model. The probiotic (109 CFU/every other day) was administered by oral gavage for 12 weeks. We found that L. plantarum ZJUIDS14 intervention significantly alleviated HFD related hepatic steatosis, liver damage, insulin resistance, and increased hepatic expression of peroxisome proliferator activated receptor α (PPAR-α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 78 publications
1
8
0
Order By: Relevance
“…HFD (manifested in hyperlipidemia) is known to trigger NAFLD by elevating TC, TG, and LDL-C levels, with a corresponding drop in host HDL-C levels (17). Interestingly, some prior studies have confirmed that reducing TC, TG, and LDL-C levels can alleviate NAFLD (18, 19,51). In this study, the HFD significantly elevated the hepatic levels of TC, TG, and LDL-C and lowered the HDL-C levels, resulting in lipid metabolism disorder.…”
Section: Discussionmentioning
confidence: 99%
“…HFD (manifested in hyperlipidemia) is known to trigger NAFLD by elevating TC, TG, and LDL-C levels, with a corresponding drop in host HDL-C levels (17). Interestingly, some prior studies have confirmed that reducing TC, TG, and LDL-C levels can alleviate NAFLD (18, 19,51). In this study, the HFD significantly elevated the hepatic levels of TC, TG, and LDL-C and lowered the HDL-C levels, resulting in lipid metabolism disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Allobaculum presented a low detection in the HFD group, quercetin supplementation in HFD significantly increased the relative abundance of these genera in NAFLD mice, [30], while our results displayed BPIS increased Allobaculum increased with BPIS treatment as compared to a control group of mice, and it correlates positively with NAFLD. In the current study Lactobacillus, Bifidobacterium, Allobaculum, and Ruminococcus genus were increased with treatment of BPIS to NAFLD mice as compared to the control group, other studies also reported Lactobacillus, Bifidobacterium genera species administered to C57BL/6 mice significantly improved HFD related hepatic steatosis, liver damage, increased hepatic expression of peroxisome proliferation activated receptors, and insulin resistance [34][35][36].…”
Section: Bpis Regulates the Gut Microbiome In C57bl/6n Micementioning
confidence: 62%
“…The results of this study were consistent with the above study ( Hassan et al, 2020 ), L. plantarum ATCC14917 can reverse the changes in the structure of the gut microbiota induced by the HFD, notably the major bacterial phylum. In recent years, many studies have shown that probiotics can regulate intestinal flora to prevent intestinal flora imbalance, improve intestinal barrier function, reduce oxidative stress and inflammation, and improve lipid metabolism and NAFLD ( Cao et al, 2022 ; Hu et al, 2022 ; Arellano-García et al, 2023 ; Shin et al, 2023 ; Wang et al, 2023 ; Zhao et al, 2023 ). In addition, there are several studies on the effects of different probiotics on improving NAFLD in clinical trials ( Arellano-García et al, 2022 ; Noormohammadi et al, 2023 ; Zhou et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%